DEVELOPMENT AND RESEARCH OF ULTRASONIC OSCILLATORY SYSTEM FOR HARDENING OF SPRING PLATE BILLETS - V. A. Tomilo (Литьë и металлургия)
Various schemes of ultrasonic oscillatory system are developed: with a «force nonsensitive» support, with a «force sensitive» support, with the deforming steel balls in bulk. Results of the ultrasonic treatment showed that hardening of a surface of the samples took place when the vibration amplitude of a radiator exceeds a certain level. The level of hardening increases with increase in amplitude of fluctuations of a radiator. Higher level of hardening is registered when the surface is treated by steel balls.